Ambidextrous Cloud Governance Approach to Enhance TelCo's Digital Transformation Using COBIT 2019 Traditional and DevOps - Andriani, Novi; Mulyana, Rahmat; Saedudin, Rd. Rohmat (Indonesian Scientific Journal, 2025)
Cloud computing plays a crucial role in accelerating digital transformation within the telecommunications sector by enhancing operational efficiency, scalability, and service innovation. However, TelCo faces difficulties in aligning its cloud adoption with effective governance, particularly in ensuring continuous service delivery and resilience. This study proposes a cloud governance framework based on the ambidextrous integration of COBIT 2019 Traditional components and DevOps Focus Area. Employing a Design Science Research methodology, data were collected through semi-structured interviews guided by a structured questionnaire and triangulated with internal documents until data saturation was achieved. Governance and Management Objectives were prioritized using the ambidextrous COBIT 2019 lens, supported by regulatory guidelines from the SOE Minister No. PER-2/MBU/03/2023 and the ICT Minister No. 5/2021, as well as relevant prior studies. The analysis highlighted DSS04: Managed Continuity as the most critical focus area. A capability gap assessment identified vacant leadership roles, overlapping responsibilities, and the lack of Infrastructure as Code (IaC) implementation in cloud services. Recommended improvements include formal assignment of leadership positions, clarification of IT responsibilities, and the adoption of IaC practices. These enhancements are expected to raise the capability maturity of DSS04 from 3.25 to 3.87, representing a 0.62 increase in business continuity readiness. This study contributes to research by extending ambidextrous governance theory to cloud continuity management and provides practical guidance for telecommunications providers seeking to improve operational resilience and manage risks effectively in their digital transformation efforts.